LINGUISTIC LANDSCAPE AND CULTURAL GLOBALIZATION: A COMPARATIVE STUDY OF SIGNAGES IN A MULTI CULTURAL ENVIRONMENT: Received: 10th January 2023; Revised: 2nd May 2023, 22nd May 2023; Accepted: 1st June 2023 - Champakaew, Wilawan; Suejam, Nattapat; Chuaychoowong, Maneerat (PUPIL: International Journal of Teaching, Education and Learning, 2023)
This research paper has two main objectives which are 1) to study signages displayed in multicultural environments and 2) to compare and contrast the similarities and differences between two multicultural areas. These two objectives have led to two research questions; (1) What are the languages displayed on signages in the two multicultural areas? And, (2) what are the functions of the signages found in the two multicultural areas? To answer these two questions, the researchers employed two main frameworks: types of signages by Siwina and Prasithrathsint (2020) and functions of signages by Yanhong and RungRuang (2013). The results show that most languages displayed on signages in the Chinese temple are bilingual, monolingual, and multilingual. On the other hand, most of the languages displayed on signages in the Hinduism temple are monolingual, bilingual, and multilingual languages. Moreover, the functions of signages found in the Chinese temple are namely, mythological (18 signages), informational (12 signages), symbolic (6 signages), requesting (2 signages), invitational (2 signages), and instructional (2 signages). Furthermore, from the Hinduism temple, a total of seven functions were found, namely, requesting (11 signages), invitational (12 signages), mythological (4 signages), ordering (3 signages), informational (2 signages), commercial (2 signages), and instructional (1 signage). This study suggested that linguistic landscape plays an important role in creating understanding among multiculturalism in religious settings.